Quo Vadis, Muslim Youth Entrepreneurship? Bibliometric Analysis of Entrepreneurship at Islamic University - Zaidi, Nurul Ain Binti; Cahyani, Utari Evy; Siregar, Rizal Ma'ruf Amidy (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Muslim youth empowerment is an issue that is not only related to the economic field but also to other fields such as education, health, sociology, and psychology. Entrepreneurship is an effort to empower Muslim youth to increase their competitiveness in the global economy. Thus, this research aims to investigate the trends in existing research on entrepreneurship at Islamic Universities. The data analyzed were from 88 research publications from 2007 to 2022 in Dimensions.ai with the search terms